2015
DOI: 10.5713/ajas.15.0840
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Physicochemical and Nutritional Properties of Breast and Thigh Meat from Crossbred Chickens, Commercial Broilers, and Spent Hens

Abstract: The objective of this study was to compare the physicochemical and nutritional properties of breast and thigh meat from commercial Chinese crossbred chickens (817 Crossbred chicken, 817C), imported commercial broilers (Arbor Acres broiler, AAB), and commercial spent hens (Hyline Brown, HLB). The crossbred chickens, commercial broilers and spent hens were slaughtered at their typical market ages of 45 d, 40 d, and 560 d, respectively. The results revealed that several different characteristic features for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
90
8
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 28 publications
19
90
8
3
Order By: Relevance
“…The major amino acids of plant protein both raw and TVP were glutamic acid, aspartic acid, proline, and leucine which were similar to that of extruded soybean/corn flour . Meanwhile, glutamic acid, aspartic acid, lysine, and leucine were identified as the major amino acids in meat samples, which were in agreement with the results for beef, pork, and chicken, where glutamic acid, aspartic acid, and leucine were the amino acids present at a higher level. The sulfur‐containing amino acids (methionine, cysteine), glutamic acid and proline of TVP were higher than that of raw material but the other amino acids were lower.…”
Section: Resultsmentioning
confidence: 99%
“…The major amino acids of plant protein both raw and TVP were glutamic acid, aspartic acid, proline, and leucine which were similar to that of extruded soybean/corn flour . Meanwhile, glutamic acid, aspartic acid, lysine, and leucine were identified as the major amino acids in meat samples, which were in agreement with the results for beef, pork, and chicken, where glutamic acid, aspartic acid, and leucine were the amino acids present at a higher level. The sulfur‐containing amino acids (methionine, cysteine), glutamic acid and proline of TVP were higher than that of raw material but the other amino acids were lower.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained from the current study indicated that greater protein denaturation occurred in BM which is more sensitive to protein denaturation than TM. This difference in protein solubility of BM and TM could be attributed to the structural diversity between thigh and BM, particularly, lower collagen content and solubility in BM than TM (Chen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The different responses of breast and thigh muscles to FSBM treatments might be due to the higher contents of total amino acids in the breast muscle, which made it more sensitive. Chen et al [37] reported that breast muscle contained higher levels of total essential and non-essential amino acids than those of thigh muscle in commercial broilers. It was demonstrated that the growth of breast muscle required higher ideal ratios of digestible methionine and threonine than leg muscle in boilers [38], which indicated the inconsistent responses of breast and leg muscles.…”
Section: Discussionmentioning
confidence: 99%